Impact of climate change environmental conditions on the resilience of different formulations of the biocontrol agent Candida sake CPA‐1 on grapes - Carbó, Anna; Torres, Rosario; Teixidó, Neus; Usall, J.; Medina, Angel; Magan, Naresh (Wiley, 2018)
Biocontrol agents have become components of integrated crop protection systems for controlling economically important fungal pathogens. Candida sake CPA‐1 is a biocontrol agent of fungal pathogens of fruits, both pre‐ and post‐harvest. While the efficacy of different formulations have been examined previously, few studies have considered the resilience of different formulations under changing climatic conditions of elevated temperature, drought stress and increased atmospheric CO2. This study examined the effect of (a) temperature × RH × elevated CO2 (400 vs 1000 ppm) on the temporal establishment and viability of two dry and one liquid C. sake CPA‐1 formulations on grape berry surfaces; (b) temperature stress (25 vs 35°C); and (c) elevated CO2 levels. Results indicated that temperature, RH and CO2 concentration influenced the establishment and viability of the formulations but there was no significant difference between formulations. For the combined three‐component factors, increased temperature (35°C) and lower RH (40%) reduced the viable populations on grapes. The interaction with elevated CO2 improved the establishment of viable populations of the formulations tested. Viable populations greater than Log 4 CFUs per g were recovered from the grape surfaces suggesting that these had conserved resilience for control of Botrytis rot in grapes.
Keywords: yeast formulations; global warming; climate change; resilience, elevated CO2; biocontrol; Botrytis cinerea